Modem view on etiology and treatment of temporomandibular disorder - K. Yu. Galebskaya (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The review is dedicated to the interrelationship between temporomandibular disorder and such factors as malocclusion, teeth alteration, dynamic occlusal factors, orthodontic treatment, position of heads of mandibular relative to glenoid fossa. Some aspects of temporomandibular disorder treatment are also discussed.